2018
DOI: 10.1177/0091026018816340
|View full text |Cite
|
Sign up to set email alerts
|

Servant Leadership, Leader–Member Exchange and Proactive Behavior in the Public Health Sector

Abstract: Very limited attention has been given by scholars to the relationship between servant leadership and employee behaviors in the public sector and not much is known about the mechanisms through which this relationship may take place. This study examines the relationship between servant leadership and proactive behaviors in the Egyptian public health sector and investigates the role of leader–member exchange (LMX) as a mediator. Using a sample of Egyptian public hospital nurses, the results of structural equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 51 publications
5
40
0
Order By: Relevance
“…On the other hand, findings of the previous studies based on the SET (Blau, 1964) have shown that servant nurse leaders enhance nurses' IBs by empowering them to create value for their workplace (Khan et al, 2020(Khan et al, , 2021Liden et al, 2008Liden et al, , 2014. These findings also confirm that SL affects nurses' proactive behaviors (Mostafa and El-Motalib, 2019) as well as their helpful and creative behaviors (Neubert et al, 2016). In addition, they are consistent with the results of the studies of employees in sectors other than nursing (Erkutlu and Chafra, 2015;Sun et al, 2016;Cai et al, 2018;Iqbal et al, 2020;Khan et al, 2020Khan et al, , 2021Su et al, 2020).…”
Section: Theoretical Contributionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, findings of the previous studies based on the SET (Blau, 1964) have shown that servant nurse leaders enhance nurses' IBs by empowering them to create value for their workplace (Khan et al, 2020(Khan et al, , 2021Liden et al, 2008Liden et al, , 2014. These findings also confirm that SL affects nurses' proactive behaviors (Mostafa and El-Motalib, 2019) as well as their helpful and creative behaviors (Neubert et al, 2016). In addition, they are consistent with the results of the studies of employees in sectors other than nursing (Erkutlu and Chafra, 2015;Sun et al, 2016;Cai et al, 2018;Iqbal et al, 2020;Khan et al, 2020Khan et al, , 2021Su et al, 2020).…”
Section: Theoretical Contributionsupporting
confidence: 85%
“…Previous studies have shown that SL has a significant relationship with employees' IBs (Erkutlu and Chafra, 2015;Sun et al, 2016;Cai et al, 2018;Iqbal et al, 2020;Khan et al, 2020Khan et al, , 2021Su et al, 2020) and creative behavior (Lee et al, 2020). Studies conducted with nurses have reported a significant relationship between SL and nurses' proactive (Mostafa and El-Motalib, 2019) and creative behaviors (Neubert et al, 2016). In the present study, three hypotheses were developed based on this theoretical rationale and empirical foundations:…”
Section: Background and Hypothesis Developmentmentioning
confidence: 90%
“…(2016) explored the relationship between authentic leadership and thriving and found significant positive relationships between vitality of staff and an authentic leadership approach. In relation to servant leadership, Mostafa and El‐Motalibs (2019) and Hanse et al. (2016) found high‐quality social exchanges and mutual trust were enhanced by servant leadership.…”
Section: Resultsmentioning
confidence: 99%
“…First, servant leaders prioritize subordinates' needs, enhancing their wellbeing (Varela et al, 2019;Panaccio et al, 2015), need for relatedness, and ultimately psychological safety (Bande et al, 2016). Under this style of leadership, the chance of being liked by one's subordinates increases, increasing subordinates' motivation to behave proactively (Mostafa and El Motalib, 2019). Second, servant leaders promote collaboration, as they work well with those who show initiative (Bande et al, 2016) and use their power in ethical ways, enhancing employees' sense of competence and autonomy.…”
Section: Servant Leadershipmentioning
confidence: 99%